2009
DOI: 10.1536/ihj.50.477
|View full text |Cite
|
Sign up to set email alerts
|

Surface ECG Characteristics of Ventricular Tachyarrhythmias Before Degeneration Into Ventricular Fibrillation in Patients With Brugada-Type ECG

Abstract: SummaryThis study was designed to evaluate whether the right ventricular outflow tract (RVOT) is the arrhythmogenic focus in Brugada syndrome. We enrolled 45 patients with Brugadatype ECG who underwent programmed ventricular stimulation and inducible ventricular fibrillation (VF). In 25 of these 32 patients, repetitive VT was observed before degeneration into VF. The QRS morphology of surface ECG and intracardiac electrograms were evaluated to determine the origin of the ventricular tachycardia (VT) that degen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…22 Previously, we recorded low-amplitude fragmented and delayed potentials at the RVOT in BS patients with inducible VF, 23 and we found that a majority of patients with BS showed repetitive VT originating from the RVOT that degenerated into VF. 17 Moreover Park et al reported that the maximum slope of the APD restitution curve in BS patients with inducible VF was 2.1 at the RVOT and significantly greater than that at the RVA (1.1). 24 To our knowledge, we provide the first description of the detailed APD restitution properties in BS.…”
Section: Ashino S Et Almentioning
confidence: 97%
See 2 more Smart Citations
“…22 Previously, we recorded low-amplitude fragmented and delayed potentials at the RVOT in BS patients with inducible VF, 23 and we found that a majority of patients with BS showed repetitive VT originating from the RVOT that degenerated into VF. 17 Moreover Park et al reported that the maximum slope of the APD restitution curve in BS patients with inducible VF was 2.1 at the RVOT and significantly greater than that at the RVA (1.1). 24 To our knowledge, we provide the first description of the detailed APD restitution properties in BS.…”
Section: Ashino S Et Almentioning
confidence: 97%
“…5,6, 29 We assessed the repolarization restitution property and showed that the maximum restitution slope in the RVOT of BS patients with inducible VF is significantly steeper than that of control patients, which indicates that the RVOT region may play an important role in the degeneration into sustained VF in patients with BS. Previous studies have also revealed the importance of the RVOT in the development of VF in BS, based on the presence of delayed potentials in the RVOT, 30 the presence of initial repetitive VT originating from the RVOT before degeneration into VF, 17 and development of spontaneous premature contractions triggering VF mainly in the RVOT. 31 Transmural dispersion of repolarization in the RVOT has been shown to contribute to initial repetitive excitation during VT in experimental BS models.…”
Section: Mechanism Of Vf In Bsmentioning
confidence: 99%
See 1 more Smart Citation
“…37) The electrical abnormality is localized in the free wall of the RVOT, as suggested by the frequent origin or induction of ventricular arrhythmia from this region, [38][39][40][41] and Haissaguerre, et al 42) showed the importance of focal premature ventricular beats, originating mainly from the RVOT, in triggering VF in patients with Brugada syndrome. Several studies based on noninvasive techniques have shown right ventricular abnormalities in patients with the clinical phenotype of Brugada syndrome.…”
mentioning
confidence: 99%
“…Two principal mechanisms are thought to be responsible for Brugada syndrome (BrS): right ventricular (RV) conduction delay 1,2) and RV subepicardial action potential shortening 3,4) . We have reported endocardial conduction delay in the RV outflow tract 5) (RVOT) that provoked ventricular tachycardia (VT), which degenerated into programmed ventricular stimulation (PVS)-inducible ventricular fibrillation (VF) with a left bundle branch block morphology 6) . However, only a few reports have described the site of origin of the provoked VT 7,8) .…”
Section: Introductionmentioning
confidence: 99%